A four-camera videogrammetric system for 3-D motion measurement of deformable object - Hu, Hao (2013)
A four-camera videogrammetric system with large field-of-view is proposed for 3-D motion measurement of deformable object. Four high-speed commercial-grade cameras are used for image acquisition. Based on close-range photogrammetry, an accurate calibration method is proposed and verified for calibrating the four cameras simultaneously, where a cross target as calibration patterns with feature points pasted on its two-sides is used. The key issues of the videogrammetric processes including feature point recognition and matching, 3-D coordinate and displacement reconstruction, and motion parameters calculation are discussed in detail. Camera calibration experiment indicates that the proposed calibration method, with a re-projection error less than 0.05 pixels, has a considerable accuracy. Accuracy evaluation experiments prove that the accuracy of the proposed system is up to 0.5 mm on length dynamic measurement within 5000 mm×5000 mm field-of-view. Motion measurement experiment on an automobile tire is conducted to validate performance of our system. The experimental results show that the proposed four-camera videogrammetric system is available and reliable for position, trajectory, displacement and speed measurement of deformable moving object.